'When I'm 65': On the Age-negotiated Duty to Work. (February 2021) - Wilińska, Monika; Rolander, Bo; Bűlow, Pia H
The duty to work is an unquestionable norm in contemporary welfare systems. Nonetheless, as argued in this article, duty to work can be negotiable, and there are age norms that can be used to loosen its otherwise rigid character. This interview-based article follows the work rehabilitation stories of 57 men and women who, in making sense of their illnesses, rehabilitation and work, recurrently use age norms to validate their accounts. In the context of heightened social pressures on paid labour, the practices of doing age seem to both validate and counterbalance the norms of paid labour. Interestingly, the use of age norms is not bounded by any age, gender or education groups; rather, it is used across various social positions. The article discusses age and age norms and their relation to the moral norms of paid labour in contemporary welfare societies.